PEMODELAN ALTERNATIF PENANGANAN PERMASALAHAN SIMPANG STAGGER (STUDI KASUS: SIMPANG MARTOLOYO KOTA TEGAL) - Mutaqin, Akhmad Alwi; Aprianto, Rizal; Hadi, Suprapto (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2025)
Simpang Martoloyo has a high traffic flow because it is the meeting point of arterial roads that include residential areas, school areas, and offices, as well as business locations, namely Pasar Anyar Martoloyo. This condition resulted in congestion and long delays. This study aims to analyze the performance of signalized intersections at Simpang Martoloyo, provide recommendations, and model traffic engineering using VISSIM software. The calculation method used is Pedoman Kapasitas Jalan Indonesia (PKJI) 2023. Based on the results of the analysis of existing conditions, Simpang Martoloyo has a service level of F with an average delay of 105.96 seconds/junior high school. The improvement of the performance of Simpang Martoloyo is carried out through several traffic engineering in the form of widening the approach to the intersection, changing the cycle time, and redesigning the number of phases. The alternative handling is selected based on the most optimal improvement in intersection performance. The redesign of the cycle time to 104 seconds with a green time of 10 seconds for each phase shows the results based on PKJI calculations that this alternative can improve intersection performance by reducing the average delay to 86.07 seconds/smp, and then based on Vissim modeling, it can reduce the average delay to 41.71 seconds. The time change between the greens is considered to be able to empty the last vehicle at the point of conflict of each last phase signal.